209: Total Breastfeeding Duration and Dental Cavities in Early Childhood. Issue 6 (1st June 2014) - Wong, PD; Parkin, PC; Birken, CS; Chen, Y; Maguire, JL
Abstract: BACKGROUND: Childhood dental cavities remain a public health challenge. Although cavities are believed to be associated with low socioeconomic status, ethnic and racial minorities, single parenting, and low parental education, the relationship of breastfeeding and cavities is likely multifactorial. There is insufficient evidence to support or refute a link between breastfeeding duration and childhood dental cavities. While breastfeeding is an important and well known preventative health practice, evidence-based information on total duration of breastfeeding is lacking. The World Health Organization recommends breastfeeding up to two years or beyond. However, the age beyond two years after which breastfeeding remains beneficial is unclear. Understanding the effect of breastfeeding duration on cavities will assist parents and clinicians in choosing the optimizing total breastfeeding duration. OBJECTIVES: The primary objective was to determine if the total duration of breastfeeding is associated with childhood dental cavities. The secondary objective was to determine if demographic, dietary, behavioural, and life-style factors modify the relationship between total duration of breastfeeding and cavities. We hypothesized that longer total duration of breastfeeding is associated with a higher incidence of childhood dental cavities. METHODS: Cross-sectional study of healthy children, aged one to five years who attended well-child visits at primary care physician's offices from September 2011 to August 2013 was conducted through the TARGet Kids! practice-based research network. Univariate and Poisson regression analyses were used to measure the association between total breastfeeding duration and childhood dental cavities. RESULTS: Survey and anthropometric data were collected from 2043 healthy children (median age 61.1 months) who met inclusion criteria. Longer total duration of breastfeeding was significantly associated with ECC (Incidence risk ratio [IRR] 1.023 per month [95% CI 1.018 to 1.029]; P<0.001). This association remained statistically significant after adjusting for potential confounders (IRR 1.018 per month [95% CI 1.011 to 1.025]; P<0.001). Significant covariates included older child (P<0.001), higher number of siblings (P=0.008), single parenting (P=0.003), lower birth weight (P=0.019), younger maternal age (P=0.021), bedtime bottle use (P=0.004), and lower family income (P<0.001). CONCLUSION: Longer total duration of breastfeeding was associated with a small but clinically relevant 2% increased risk of dental cavities per month of breastfeeding beyond one year of age.